DIAGNOSTIC SIGNIFICANCE OF BIOMARKERS IN THE EARLY STAGES OF RENAL FAILURE - Salokhiddinov Eldor Shukhratjon ugli (Web of Journals Publishing, 2025)
The detection of renal dysfunction before irreversible damage occurs remains a critical challenge in clinical nephrology. Traditional markers demonstrate limited sensitivity during initial phases of kidney injury. This investigation examined emerging biomarkers in patients with stage 1-2 chronic kidney disease, comparing their diagnostic performance against conventional parameters. Analysis of 284 patients revealed that novel markers, particularly neutrophil gelatinase-associated lipocalin and cystatin C, demonstrated superior sensitivity for detecting subtle functional changes. Early identification through these biomarkers enables timely therapeutic intervention, potentially altering disease trajectory before advanced pathological changes become established.
Keywords: nephrology, renal failure, cystatin C, neutrophil gelatinase-associated lipocalin, kidney injury molecule-1, interleukin-18, creatinine.